P1458 Recurrent endocarditis on mitral valve prosthesis. (17th January 2020) - Suma, S; Spaziani, C; Manca, T; Ramelli, A; Vezzani, A; Nicolini, F; Gherli, T; Brambilla, V; Sartorio, D; Botti, A; Cozza, F; Garibaldi, S; et al.
Abstract: : Patient Presentation and initial work up A 72 years old man with history of hypertension was admitted to our hospital due to acute pulmonary oedema. He had no fever at that time and he had an history of known mitral valve prolapse but with no reported mitral valve regurgitation (MR). Transthoracic Echocardiogram (TTE) was performed and it showed a severe MR. Transesophageal echocardiogram (TOE) showed prolapse of the posterior leaflet of the mitral valve with suspicion of cordal rupture and the presence of an aneurysm of the anterior mitral valve leaflet with perforation of it (panel A and B). Diagnosis and Management Diagnosis of severe MR as the result of previous endocarditis was made. Blood cultures were negative, as well as there were no signs of active endocarditis. However, since there were heart failure and signs of uncontrolled infection, the patient underwent surgical mitral valve replacement (MVR) with bioprosthesis. Moreover, it was started antibiotic therapy with vancomycin, rifampin and ceftriaxone, which was continued for two weeks and then stopped since the microbiological culture of the valve was negative. Follow-up After two months he was re-admitted to the hospital due to a new onset of breathlessness. TTE showed a dehiscence of the mitral prosthetic valve in the inferolateral zone with rocking movement, subvalvular pseudoaneurysm and moderate paravalvular leak (panel C and D). Blood cultures were positive for Staphylococcus Aureus. Consequently, the patient underwent a new surgical MVR. Furthermore, six weeks of antibiotic therapy were carried out with daptomycin and rifampin. However, after another three months, he was admitted once again to the hospital for heart failure with a new evidence of abruption of the mitral prosthesis, again in the inferolateral region and, this time, with the evidence of a vegetation on the atrial side of the prosthesis (panel E and F). Again, blood cultures were positive for Staphylococcus Aureus, and the patient underwent the third surgical intervention of MVR. Another six weeks of antibiotic therapy with daptomycin and rifampin were performed. The patient was then discharged and he is now strictly followed clinically. Conclusion: In conclusion, we reported the case of a recurrent relapse of endocarditis on mitral valve prosthesis due to Staphylococcus Aureus infection. Interestingly, the mitral prosthesis was involved always in the same zone (inferolateral area) with abruption of the prosthesis and significant paravalvular regurgitation. At the second relapse there was also a vegetation on it and both times blood cultures were positive. Moreover, antibiotic therapy was conducted for six weeks both times, but the recurrence of endocarditis showed us that he was a sensitive patient and that in cases of relapses like this it should be performed a more careful clinical follow up, involving frequent laboratory tests and clinical and echocardiographic evaluations.